DPP‐4 Inhibition Attenuates Cardiac Dysfunction and Adverse Remodeling Following Myocardial Infarction in Rats with Experimental Diabetes. Issue 5 (12th September 2013) - Connelly, Kim Alexander; Zhang, Yanling; Advani, Andrew; Advani, Suzanne L.; Thai, Kerri; Yuen, Darren A.; Gilbert, Richard E.
Summary: Aims: Following myocardial infarction (MI), individuals with diabetes have a two‐fold increase in the risk of heart failure, due in part to excessive loss of cardiac microvasculature. Endothelial integrity and restitution are mediated in part by stromal cell–derived factor‐1α (SDF‐1α), a chemokine that is elaborated by ischemic tissue but rapidly degraded by dipeptidyl peptidase‐4 (DPP‐4). Accordingly, we hypothesized that inhibiting this enzyme may confer benefit following myocardial infarction in the diabetic setting beyond its effect on glycemia. Methods and Results: Fischer F344 rats with streptozotocin (STZ)‐diabetes were randomized to receive vehicle or the DPP‐4 inhibitor, sitagliptin (300 mg/kg/day). Two weeks later, animals underwent experimental MI, induced by ligation of the left anterior descending coronary artery. Cardiac function was assessed by conductance catheterization and echocardiography along with cardiac structure 4 weeks post‐MI. Following MI, untreated diabetic rats developed both systolic and diastolic cardiac dysfunction, in association with endothelial cell loss, fibrosis, and myocyte hypertrophy. Without affecting plasma glucose, sitagliptin treatment led to an improvement in passive left ventricular compliance, increased endothelial cell density, reduced myocyte hypertrophy, and a reduction in the abundance of collagen 1 (all P  < 0.05). Systolic function was unchanged. Conclusions: This study shows that DPP‐4 inhibition attenuates several, but not all, aspects of cardiac dysfunction and adverse remodeling in the post‐MI setting.